2015
DOI: 10.1261/rna.049130.114
|View full text |Cite
|
Sign up to set email alerts
|

Three CRISPR-Cas immune effector complexes coexist in Pyrococcus furiosus

Abstract: CRISPR-Cas immune systems function to defend prokaryotes against potentially harmful mobile genetic elements including viruses and plasmids. The multiple CRISPR-Cas systems (Types I, II, and III) each target destruction of foreign nucleic acids via structurally and functionally diverse effector complexes (crRNPs). CRISPR-Cas effector complexes are comprised of CRISPR RNAs (crRNAs) that contain sequences homologous to the invading nucleic acids and Cas proteins specific to each immune system type. We have previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 76 publications
6
68
0
Order By: Relevance
“…S1). The effector complexes in P. furiosus use crRNAs produced from seven shared CRISPR loci (Majumdar et al 2015). Using deletion strains containing a single CRISPRCas system, we found that the P. furiosus Type I-A Csa and Type I-G Cst systems silence plasmid DNA invaders in a PAM-dependent manner (Elmore et al 2015).…”
Section: Resultsmentioning
confidence: 97%
“…S1). The effector complexes in P. furiosus use crRNAs produced from seven shared CRISPR loci (Majumdar et al 2015). Using deletion strains containing a single CRISPRCas system, we found that the P. furiosus Type I-A Csa and Type I-G Cst systems silence plasmid DNA invaders in a PAM-dependent manner (Elmore et al 2015).…”
Section: Resultsmentioning
confidence: 97%
“…Some systems co-existing in the same species have been demonstrated to share the same set of guides, e.g. Type III-A (Csm) and Type III-B (Cmr) of Thermus thermophilus [83], Type III-B (Cmr), Type I-A (Csa) and Type I-G (Cst) of Pyrococcus furiosus [84]. Given that the Type III loci usually lack cas6 genes, a single stand-alone Cas6 nuclease is likely to be responsible for the supply of crRNAs to the Type III complexes in T. thermophilus [83].…”
Section: Biogenesis Of Crrnasmentioning
confidence: 99%
“…Given that the Type III loci usually lack cas6 genes, a single stand-alone Cas6 nuclease is likely to be responsible for the supply of crRNAs to the Type III complexes in T. thermophilus [83]. In P. furiosus, Cas6 nuclease of Type I generates the crRNAs from all CRISPR loci for the different co-existing complexes [84]. Cas6-based processing of pre-crRNA in Type III systems is typically followed by a sequence-unspecific trimming at the 3' end (by yet to be identified RNases) to yield mature crRNAs with a defined 8-nt 5' end and a variable 3' end [34,85,86].…”
Section: Biogenesis Of Crrnasmentioning
confidence: 99%
“…The hyperthermophilic archaeon Pyrococcus furiosus (Pfu) harbors three coexisting immune effector crRNP complexes: Type I-A (Csa), Type I-G (Cst), and Type III-B (Cmr), along with seven functional CRISPR loci (Hale et al 2008;Terns and Terns 2013;Majumdar et al 2015). There is evidence that the Pfu Csa and Cst effector complexes target DNA (Elmore et al 2015), while the Cmr complex has been shown to target DNA and RNA in vitro and in vivo (Hale et al 2009(Hale et al , 2012Deng et al 2013;Spilman et al 2013;Benda et al 2014;Ramia et al 2014;J Elmore, N Sheppard, R Terns, and M Terns, unpubl.…”
Section: Introductionmentioning
confidence: 99%